Pierre Robin Sequence: airway management via mandibular distraction. Case report. - Hernán Arango Fernández; Martha Rebolledo Cobos; Saulo Pineda Ovalle; Jonathan Harris Ricardo (Universidad de Concepción., 2019)
Pierre Robin sequence is a set of congenital conditions characterized by the presence of micrognathia, glossoptosis, cleft palate and obstruction of the airways. The latter can lead to many other complications such as respiratory difficulties, apnea, weight loss and even death. Currently, mandibular distraction, or the lengthening of the mandibular bone, is the most common surgical procedure used to correct a retracted tongue and the airway obstruction it produces in patients with mandibular hypoplasia. The present paper reports the case of a 26-day-old male patient, who presented obstruction on the upper respiratory tract, mandibular retromicrognathia, and retracted tongue and cleft palate, all conditions characteristic to Pierre Robin sequence. The patient also had a medical record of orotracheal intubation due to respiratory difficulties. The subject underwent mandibular distraction surgery with a horizontal vector, which resulted in a satisfactorily cleared airway.